Open data and open science - Morais Pires, Carlos (Technical Centre for Agricultural and Rural Cooperation, 2013)
The G8 International Conference on Open Data in April 2013 aimed to make agricultural research more widely available to improve global food security. Carlos Morais Pires from the European Commission discusses the EC's effort to increase access to data and reviews the G8's plans.